CONTINUE TO REINVENT FOR A SUSTAINED GROWTH - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 11 January 2017 The Asia Leadership Conference (ALC) 2017 rounded off its programme firstly with a short presentation by a Harvard Kennedy School of Government scholar and MPA candidate, Rahul Srinivasan at the Universiti Sains Malaysia (USM) Dewan Budaya.